2015
DOI: 10.2175/106143015x14212658614270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Full‐Scale Water‐Based Scrubber for Removing Siloxanes from Digester Gas: A Case Study

Abstract: E v a lu a tio n of a F u ll-S c a le W a te r-B a s e d S c ru b b er fo r R e m o v in g S ilo x a n e s fro m D ig e s te r Gas: A C ase S tudySharon C. Surita1 *, Berrin Tansel2A B S T R A C T : Siloxanes are becoming more prominent in digester gas at water resource recovery facilities because of their wide use in personal care products. This study evaluates a full-scale water-based scrubber operating in a water resource recovery facility (Miami, FL). The digester gas is used for energy generation due to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Reactive absorption processes are capable of converting siloxanes into less volatile compounds, but they require the use of harsh absorption agents (e.g., nitric acid and/or sulfuric acid), something that significantly increases the cost and technical complexity associated with these processes . Physical absorption techniques involve less toxic chemicals but, on the other hand, are not all that effective for the removal of light siloxanes (e.g., L 2 ) due to their high volatilities . Such volatile siloxane pollutants often require relatively high pressures to achieve high removal efficiencies. , Additionally, physical absorption processes also suffer from similar disadvantages with the competing adsorption techniques: (i) the need for absorbent regeneration, which can reduce siloxane removal efficiencies over time due to the accumulation of siloxanes (or decomposition byproducts) inside the absorbing medium from successive regeneration cycles; (ii) the fact that the siloxanes are released intact during the regeneration process and must be properly disposed of.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive absorption processes are capable of converting siloxanes into less volatile compounds, but they require the use of harsh absorption agents (e.g., nitric acid and/or sulfuric acid), something that significantly increases the cost and technical complexity associated with these processes . Physical absorption techniques involve less toxic chemicals but, on the other hand, are not all that effective for the removal of light siloxanes (e.g., L 2 ) due to their high volatilities . Such volatile siloxane pollutants often require relatively high pressures to achieve high removal efficiencies. , Additionally, physical absorption processes also suffer from similar disadvantages with the competing adsorption techniques: (i) the need for absorbent regeneration, which can reduce siloxane removal efficiencies over time due to the accumulation of siloxanes (or decomposition byproducts) inside the absorbing medium from successive regeneration cycles; (ii) the fact that the siloxanes are released intact during the regeneration process and must be properly disposed of.…”
Section: Introductionmentioning
confidence: 99%
“…A study at a full-scale WWTP indicated that scrubbers employed for H2S removal did not provide effective removal of siloxanes and post-scrubber treatment was needed to remove siloxanes from the digester gas prior to combustion (Surita and Tansel, 2015). Kajolinna et al (2015) investigated the efficiency of three different siloxane removal systems: activated carbon (AC), silica gel, and molecular sieve based systems.…”
Section: Physiochemical Odor/emissions Control Methodsmentioning
confidence: 99%
“…Current technologies for the removal of siloxanes from biogas include adsorption onto activated carbon (being largely applied at full-scale) or solvents (wet scrubbing) [153], chilling and condensation [154], membrane filtration [155] and biodegradation [150]. Sludge pretreatment methods such as pre-aeration [156], pre-digestion [152] and thermal pretreatment with biogas stripping [157] were shown to be effective at lab-scale level for siloxane removal before AD, therefore reducing the need of biogas treatment.…”
Section: Siloxanesmentioning
confidence: 99%